PENGARUH JENIS MULSA DAN DOSIS PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MELON (Cucumus melo L.) - Mita Setyowati; Teuku Sarwanidas; Maimunsyah Maimunsyah (Universitas Teuku Umar, 2018)
Melon plants is one of the selling price of horticultural commodities are relatively good and it was a lot of consumer demand. Therefore, the general market outlook for commodities is quite good, so the development deserves attention. As efforts to increase growth and yield of melon, needs to be done ballanced fertilization with NPK fertilizer. Mulching intended to preserve agricultural land by using organic materials, inorganic and remnants of harvest. This study aims to determine the effect of mulch type and dose of NPK fertilizer on growth and yield tangible melon and whether or not the advance of the second interaction of these factors. Research conducted at the Village Cot Kuta, District Likes Makmue Nagan Raya district, on September 25, 2014 to December 20, 2014. This study used a randomized block design (RAK) with a 3x3 factorial design, consisting of two factors: the type and dose of NPK fertilizer mulch. Factors types of mulch consists of three levels ie straw mulch, black plastic mulch silver and a bunch of mulch palm. Factor NPK fertilizer dose consists of three levels ie 40 grams per plant, 80 grams per plant and 120 grams per plant. The parameters analyzed include plant height, number of nodes, segment length, days to flowering, fruit number and fruit weight. The results showed that the growth and production of the best melon found in each factor silver black plastic mulch treatment and dosage of NPK fertilizer 80 grams per plant.Keywords: growth, melon, NPK, type of mulch